KETANGGUHAN PANCASILA SEBAGAI IDEOLOGI BANGSA INDONESIA DI ERA REVOLUSI INDUSTRI 4.0 - Rahma, Hanum Lauditta; Habibah, Siti Maizul (Jurnal Kalacakra: Ilmu Sosial dan Pendidikan, 2024)
The era of disruption that occurred globally had affected all human life in various fields, both  in the economic, social, cultural, political, educational and other fields. Pancasila as the basis of the  state and as the nation's view of life, must not be abandoned in order to achieve the values of the  precepts contained in Pancasila. Pancasila holds an important role to be a filter of new values by  applying the values of Pancasila in all aspects of life. The research method used in this article is  qualitative research and library research method. The industry 4.0 with all the disruptions that  follow needs to be addressed critically by living the values as one of the foundations that are  maintained in the disruption of the industry 4.0.